2021
DOI: 10.7759/cureus.18825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-Esteem and Self-Perceived Body Image on the Acceptance of Cosmetic Surgery

Abstract: BackboardCosmetic surgery is the preservation, rebuilding, or improvement of the physical appearance of an individual through surgical and non-surgical methods. In the last few years, an increase in the number of cosmetic procedures was noticed worldwide. This increase suggests due to multifactorial changes in people's attitudes towards cosmetic surgery and concern about their physical appearance. This study aims to assess the impact of self-esteem and self-perceived body image on the acceptance of cosmetic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
10
1
6
Order By: Relevance
“…Our study's overall ACSS score was 52. [17]. This enormous disparity between our results can be attributed to the difference in the mean age of the research participants, as it was reported that acceptance of cosmetic interventions is remarkably higher in older age groups [15,18].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our study's overall ACSS score was 52. [17]. This enormous disparity between our results can be attributed to the difference in the mean age of the research participants, as it was reported that acceptance of cosmetic interventions is remarkably higher in older age groups [15,18].…”
Section: Discussioncontrasting
confidence: 59%
“…Morait et al reported a mean ACSS score of 60.11±25.11 among 389 adults in Riyadh, with a mean age of 29 years old [ 14 ]. Additionally, Al Ghadeer et al found a mean ACSS score of 58.2±20.5 among 1008 adults in the Eastern Province, with a mean age of 34 years old [ 17 ]. This enormous disparity between our results can be attributed to the difference in the mean age of the research participants, as it was reported that acceptance of cosmetic interventions is remarkably higher in older age groups [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in cosmetic surgery has been linked to a variety of epidemiological, social media, and psychological factors that could influence an individual’s motivation for cosmetic surgery. 67 , 68 The demand for cosmetic operations is increasing worldwide, particularly in East Asian countries and among ethnic minorities. 9 Women are likelier to undertake cosmetic surgery than men, 6 and lower self-ratings of physical beauty indicate a higher prevalence of cosmetic surgery being undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Among female participants 86%, and among male participants, 84% reported at least one disliked facial/body feature. Similarly, few recent studies published during and after the COVID-19 pandemic in Saudi Arabia found no significant association between gender and cosmetic procedure demand [ 25 , 26 ]. Thus, a noticeable aesthetic concern was found among male participants, which could be explained by the video conferencing impact on appearance satisfaction.…”
Section: Discussionmentioning
confidence: 99%